MEKANISME PRODUK TABUNGAN SIMPEL (SIMPANAN PELAJAR) DI PT BANK MAYAPADA INTERNASIONAL Tbk - Refa Gustia; Choirunnisak Choirunnisak (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2021)
This research discusses how the mechanism of the SIMPLE (student savings) savings product at Bank Mayapada Internasional Palembang. This research method is interview. The results of this study are: These savings are intended for PAUD, kindergarten, elementary, junior high, high school, madrasah students who are under 17 years of age and do not have a KTP. To open an account, only use NIS (Student Identification Number) or NIK (Identity Number) and family card (KK).